Licensing interim R&D knowledge - Yossi Spiegel (Northwestern University, Center for the Study of Industrial Organization (CSIO), 2007)
This paper considers three firms that engage in an R&D contest to develop a new profitable technology. For a broad range of parameters, the firm that leads the contest (i.e., has the highest probability of success) is better-off licensing or selling its superior interim knowledge to one of the two lagging firms or to both rather than holding on to its lead. Although transferring interim R&D knowledge to the lagging firms erodes the technological lead of the leading firm, it allows it to extract rents from its rivals and can possibly create value by increasing the chance that the licensee(s) will develop the new technology when the leading firm fails.
Keywords: D45; O32; 330; Interim R&D knowledge; exclusive and nonexclusive licensing; transfer of knowledge; cross-licensing; Innovationswettbewerb; Lizenzvergabe; Wissenstransfer